Enantioselective addition of Grignard reagents to aldehydes - Englebienne, P. (2000)
The addition of Grignard reagents to aldehydes in the presence of chiral aminoal-cohols shows a moderate enantioselectivity. The study carried out with a series of ligands allows the correlation between the structural characteristics and their reactivity.